The Effect of Sensory Reweighting on Postural Control and Cortical Activity in Parkinson's Disease: A Pilot Study - Maryam Sadeghi, MS; Thomas Bristow, BS; Sodiq Fakorede, BS; Ke Liao, PhD; Jacqueline A. Palmer, PhD; Kelly E. Lyons, PhD; Rajesh Pahwa, MD; Chun-Kai Huang, PhD; Abiodun Akinwuntan, PhD; Hannes Devos, PhD (Archives of Rehabilitation Research and Clinical Translation)
Objective: To investigate the effects of sensory reweighting on postural control and cortical activity in individuals with Parkinson's disease (PD) compared to age-matched controls using a virtual reality sensory organization test (VR-SOT). Design: Cross-sectional pilot study. Setting: University research laboratory. Participants: Ten participants with idiopathic Parkinson's disease and 11 age- and sex-matched control participants without neurologic disorders. Interventions: Not applicable. Main Outcome Measures: Changes in center of pressure (COP) and electroencephalography (EEG) activity (ie, power) in the alpha band and the theta/beta ratio recorded during the VR-SOT were the main outcome variables. Results: PD participants exhibited greater COP displacement, particularly in the mediolateral direction across sensory conditions. They also showed increased alpha power when relying on visual inputs and increased theta/beta ratio power when depending on somatosensory inputs. Conclusion: PD affects sensory reweighting mechanisms involved in postural control, as evidenced by greater COP displacement and altered cortical activity. These findings emphasize the potential of EEG and VR-SOT in understanding and monitoring postural control impairments in PD.